VARK LEARNING SEBAGAI INOVASI PEMBELAJARAN: PENGARUH KEAKTIFAN, MOTIVASI, TERHADAP STRUKTUR KOGNITIF MAHASISWA - Yusak Suharno; Eko Andy Purnomo; Nurmawati Nurmawati (Universitas Muhammadiyah Semarang, 2025)
This study aims to analyze the effect of learning activity and motivation on students' cognitive structure through the implementation of VARK (Visual, Auditory, Reading, Kinesthetic) Learning-based learning. The research method uses a quantitative approach with a quasi-experimental design. The sample of this study was students majoring in Elementary School Teacher Education (PGSD) at UT in a study group in Kendal Regency who took the Educational Statistics course. The research instruments included a learning motivation questionnaire, an activeness observation sheet, and a test to measure cognitive structure. The results of the study provide an overview of the role of VARK Learning media in increasing student engagement while strengthening their cognitive structure. Based on the analysis, it was concluded that 1). the effect of motivation on cognitive structure was 71.4% 2). the effect of activeness on students' cognitive structure was 60.1%, and 3). the effect of motivation and activeness on cognitive structure was 73.3%. The conclusion was that the implementation of VARK Learning media had a significant effect between motivation and activeness on cognitive structure. Further research is expected to enable lecturers to implement VARK Learning for a wider research sample and courses other than Educational Statistics.